Factors contributing to the Lithuanian language maintenance in emigrant family: a case of US - Jakaitė-Bulbukienė, Kristina (Taikomoji kalbotyra, 2015)
When two languages collide in the context of emigration, the heritage language is in danger of extinction because the two languages are different in size, power, vitality and prestige. The question then arises why some ethnic communities maintain their language, despite the fact that their situation is disadvantageous. The main aim of this paper is to explore specific factors that help maintain the Lithuanian language in the emigrant family.This paper analyses the data collected during the research project The Language of Emigrants. Only a subset of the data that is related to the United States was selected for research. This paper analyses linguistic attitudes of two emigration waves (those who moved after World War II and those who went there after the Restoration of Lithuania’s Independence) and three generations of emigrants. This investigation is based on a quantitative survey (n = 438) and qualitative in-depth semi-standardized interviews (n = 15) from the US (most of them were recorded in May 2012 in Los Angeles, CA).The data from the quantitative survey and in-depth semi-standardized interviews shows that a successful maintaining of the Lithuanian language depends on many factors: historical circumstances, reasons for emigrating, attitude towards Lithuania, perception of identity and roots, knowledge about the history of Lithuania, the history of one’s family, and about Lithuanian traditions. If the attitude towards Lithuania is positive, if it is important for the person to be Lithuanian, if the person is knowledgeable about the history of his/her family and about Lithuanian traditions, the prospects for maintaining the heritage language are favourable.The main reasons to maintain the Lithuanian language are ideological. The data from this research shows that all waves of emigrants find it important that Lithuanian language proficiency helps preserve the Lithuanian language and culture. It is no less important to note that participants have expressed a wish to protect the Lithuanian language; they want to keep it “clear”, “true” and “pure”. Another reason to maintain the Lithuanian language is the wish to have two worlds, two familiar countries and two cultures. Naturally, there are also several practical reasons: it is useful to know several languages, to communicate with Lithuanians in Lithuanian. The Lithuanian community in the US and maintaining ties with it are also very important for language maintenance.
Keywords: family language policy; language ideology; language attitudes; language maintenance; wave of emigration